Managerial capabilities, learning orientation and performance of international halal industry using upper echelon theory - Ismail, Mazida; Mohamad, Norhidayah; Ahamat, Amiruddin (Universiti Malaysia Sarawak, 2023)
Upper echelon theory (UET) emphsizes the role of management in determining firm strategy that can lead to performance. Many studies have been conducted on UET but very few have addressed UET in international business research, especially in the halal industry. Implementing learning orientation as a culture can serve as a medium in transferring tacit knowledge within the firm. Therefore, this research was conducted to examine the mediating effect of learning orientation between managerial capabilities and international firm performance of small and medium-sized enterprises (SMEs) in the halal industry. This is a quantitative, cross-sectional study with a total of 136 responses analyzed using PLS-SEM. The results show that the impact of top-management team’s (TMT) knowledge of foreign markets on international firm performance depends on learning orientation and partially mediates the relationship between TMT’s international experience and international firm performance. The study is novel in that it tests UET in the halal industry and introduces a new mediator to the UET framework.